Job stress and depression symptoms in middle-aged workers—prospective results from the Belstress study - Clays, Els; De Bacquer, Dirk; Leynen, Francoise; Kornitzer, Marcel; Kittel, France; De Backer, Guy (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVE ': 'The aim of this study was to explore the prospective relation between job stress and symptoms of depression within a cohort study. ' ' METHODS ': 'Altogether 2821 workers were involved in the longitudinal Belstress study (Belgian job stress study); there were two measurements with a mean follow-up time of 6.6 years. Job stress was assessed by the Job Content Questionnaire. Depression symptoms were assessed by the Iowa form of the Center for Epidemiological Studies–Depression Scale. Baseline and repeated exposures to job stress were related to the development of high levels of depression symptoms through logistic regression analysis. ' ' RESULTS ': 'Within a population free of high depression scores at baseline, job stress increased the risk of developing high levels of depression symptoms after a mean follow-up time of 6.6 years. Independent associations were found for low decision latitude, high job strain, and isolated strain among women, but not among men. The adjusted association with high job strain among men was borderline significant. Repeated high job strain was associated with a more elevated risk of developing high levels of depression symptoms among both the women and the men. ' ' CONCLUSIONS ': 'The results of this study confirm that job stress is a risk factor for developing symptoms of depression. Stronger associations were found for women. The impact of high job strain among both men and women was more harmful when there was repeated exposure.
Keywords: Belstress study; depression symptom; job stress; longitudinal study; mental health; middle-aged worker; strain; work; work stress